CORM QUALITY OF TARO UNDER IRRIGATION LEVELS AND DIFFERENT SOIL TYPES - Li, Meiling [UNESP]; Deus, Angélica Cristina Fernandes [UNESP]; Ming, Lin Chau [UNESP]; Barbosa, E Aline Gonçalves [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2022)
Irrigation amount is an important factor in the development of taro, however, there is little information focus on effects of water levels affect on its corm quality under different soil textures. Thus, this study aimed to evaluate the taro corm quality in response to five irrigation levels (20%, 60%, 100%, 140% and 180% ETc-crop water requirement) under three soil textures. Results indicated that corm number total (CNt) and diameter (CD) of taro decreased with reduced irrigation levels, higher values were detected at 140%ETc and 180%ETc. CD and CNt performed better in sandy soil than in other two soils, especially in irrigation level lower than 100%ETc. In general, total sugar (TS), reducing sugar (RS), and starch content (SC) of taro corm performed better in higher water regime, except that for protein content (PC). Taro corm had higher TS and SC in sandy soil, while lower PC was observed in the same soil treatment. Overall, higher water level was more beneficial to improve corm quality, and SS could be more suitable for taro cultivation under water stress.
QUALIDADE DO TUBÉRCULO DO INHAME SOB NÍVEIS DE IRRIGAÇÃO E DIFERENTES TIPOS DE SOLO
Keywords: colocasia esculenta l. schott; soil texture; water stress